2013
DOI: 10.1177/1049909113490227
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Different Dimensions of Burden for Risk of Complicated Grief in Caregivers of Terminally Ill Patients

Abstract: The aim of the study was to test whether high levels of caregiver burden, as other confirmed predictors, are associated with the risk of prolonged grief disorder in caregivers of terminally ill patients. A predictive study was carried out in order to test the hypothesis. A demographic schedule, the Prolonged Grief 12 (PG-12), the Toronto Alexithymia Scale, Hamilton Anxiety Rating Scale, Hamilton Depression Rating Scale, and Caregiver Burden Inventory were administered to 60 caregivers of 51 patients who were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…The co-occurrence of seemingly conflicting results may also indicate that the cumulative stress perspective and stress reduction perspective do not necessarily mutually exclude each other. The presented findings are consistent with current research concerning bereavement after loss due to other illnesses, insofar as that some studies found a negative impact of CB, [74][75][76] whereas others found none. 77 The found effects are also in line with studies examining the effect of interventions targeted at reducing CB, which found a beneficial effect on mental health during caregiving 78,79 and after bereavement.…”
Section: Discussionsupporting
confidence: 92%
“…The co-occurrence of seemingly conflicting results may also indicate that the cumulative stress perspective and stress reduction perspective do not necessarily mutually exclude each other. The presented findings are consistent with current research concerning bereavement after loss due to other illnesses, insofar as that some studies found a negative impact of CB, [74][75][76] whereas others found none. 77 The found effects are also in line with studies examining the effect of interventions targeted at reducing CB, which found a beneficial effect on mental health during caregiving 78,79 and after bereavement.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (Bevans & Sternberg, ; Lai et al., ), the correlation analysis showed that the burden of caregiver was positively associated with the psychological outcome variables. The level of the caregiver burden was associated with increased levels of anxiety and depression experienced by caregivers during assistance and with an increase of risk of complicated grief.…”
Section: Discussionsupporting
confidence: 89%
“…Lai et al. () investigated the predictive role of caregivers’ burden dimensions on complicated grief in caregivers of terminally ill patients. The results showed that feeling of deprivation of existential expectations represented the greater risk factor for prolonged grief disorder among the burden dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 g Communication about illness and death. 22 was a key risk factor of adverse bereavement outcome in caregivers regardless of their preloss state of depressive symptoms.…”
Section: Discussion Of Findingsmentioning
confidence: 98%
“…10,17 Depressive symptoms in caregivers before the death of the patient have consistently been associated with adverse bereavement outcome. 1,2,4,5,14,18 A few existing studies have investigated factors related to caregiving at the end of life: severe grief symptoms during caregiving, 15,19,20 high caregiver burden, 21,22 and low preparedness for the impending death was found to be associated with adverse bereavement outcome. 23 Diverging results have been found regarding the extent of communication in the family about illness and death.…”
Section: Introductionmentioning
confidence: 99%